Renewable Energy and CO2 Emissions: Analysis of the Life Cycle and Impact on the Ecosystem in the Context of Energy Mix Changes - Sebastian Sobczuk; Agata Jaroń; Mateusz Mazur; Anna Borucka (Energies, 2025)
This study provides a comprehensive life-cycle assessment (LCA) of renewable energy sources, focusing on the <semantics>CO2</semantics> emissions and ecological impacts associated with photovoltaic (PV) systems and wind energy technologies. The research evaluates emissions from raw material extraction, production, operation, and disposal, as well as the role of energy-storage systems. Photovoltaic systems exhibit life-cycle <semantics>CO2</semantics> emissions ranging between 28–100 [g <semantics>CO2</semantics>eq/kWh], influenced by factors like production energy mix and panel efficiency. Wind turbines demonstrate lower emissions, approximately 7–38 [g <semantics>CO2</semantics>eq/kWh], with variations based on turbine type and operational conditions. Despite low operational emissions, the full environmental impact of renewables includes biodiversity disruptions, land use changes, and material recycling challenges. The findings highlight that while renewable technologies significantly reduce <semantics>CO2</semantics> emissions compared to fossil fuels, their ecological footprint necessitates integrated sustainability strategies. The analysis supports policymakers and stakeholders in making informed decisions for a balanced energy transition, emphasizing the need for continued innovation in renewable technology life-cycle management.